Kourion Urban Space Project: Preliminary Report of the 2016 Season - Swantek, Laura A.; Davies, Thomas W.; Davey, Christopher J.; Weir Jr., William J. (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
The 2016 season of the Kourion Urban Space Project (KUSP) focused on the excavation of a structure situated to the southwest of the Earthquake House on the city’s acropolis. Excavation revealed a large building, designated Building 4, that had been damaged suddenly and further decayed over time. Though it is uncertain if Building 4 was a domestic structure, administrative facility or both, it is evident from the construction materials, particularly marble and painted plaster wall facing, and imported finds that it served elite members of the Kourion community. This paper provides a preliminary description and analysis of the archaeology of Building 4. It was lodged with the Department of Antiquities, Cyprus, in January 2018 and is published here with the authors’ affiliations as they were then.